Nutrition imbalance in Chinese chronic kidney disease children. Issue 9 (5th September 2018) - Wang, Ke; Jiang, Yeping; Lai, Yuting; Shen, Ying
Abstract: Background: Nutrition imbalance is common in chronic kidney disease (CKD) children. This study evaluated the nutrition status of CKD children at different stages using bioimpedance analysis (BIA) compared with anthropometry. Methods: Fifty‐five CKD children at stages III, IV, V and 19 age‐ and sex‐matched healthy controls were recruited. Fat, protein and mineral composition on BIA were analyzed together with anthropometry for height, weight and body mass index (BMI). Biochemistry was also checked in CKD children. Results: Of the CKD children, 23.6%, 10.9% and 56.3% were underweight, overweight/obese and stunted, respectively. On BIA, 52.7%, 70.9%, 14.5% and 40.0% of the CKD children had protein reduction, fat reduction, fat enhancement and mineral reduction, respectively. Growth retardation and nutrition reduction became remarkable at stages IV and V. Approximately 65% of healthy‐weight children had nutrition reduction. In the underweight and healthy‐weight groups, fat reduction rates were higher than protein reduction rate. In the overweight/obese group, fat enhancement was most notable. Mineral reduction was less remarkable. Conclusions: The nutrition imbalance in CKD children on BIA correlated well with anthropometry and disease process, supporting BIA as an auxiliary diagnosis tool.